The Journal Of Muamalat and Islamic Finance Research : The Importance of National Poverty Eradication Programme (NAPEP) on Income Improvement and Women Empowerment :Evidence From Kwara State,Nigeria - Abdussalam O. Isiaka, Fuadah Johari (UNIVERSITI SAINS ISLAM MALAYSIA (USIM), 2015)
Greater concern has been given to women as they are being consideredas victim or prey of poverty by the international community as well as in Nigeria